2021
DOI: 10.1186/s40364-021-00263-2
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of ZHX1 and ZHX2 impacts on the prognosis of chronic lymphocytic leukemia

Abstract: Experimental evidence points to the role of Zinc fingers and homeoboxes protein 1 and 2 (ZHX1 and ZHX2) in the development and progression of several types of cancer, including hematological malignancies. Here, we determined whether the altered expression of ZHX1 and ZHX2 has clinical implications in patients with CLL. Interestingly, CLL patients with low expression ZHX1 and ZHX2 presented higher WBC counts. Importantly, our data showed that CLL patients with cytogenetic alterations presented reduced transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studies in hepatocarcinoma cells reported that ZBTB7A may regulate neural development [104], while Zou et al described Zc3h8 as a repressor of inflammation in zebrafish [105]. ZHX1 and ZHX2 participate in the development and progression of several types of cancer, and the low expression of both impacts a poor prognosis in chronic lymphocytic leukemia [106].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in hepatocarcinoma cells reported that ZBTB7A may regulate neural development [104], while Zou et al described Zc3h8 as a repressor of inflammation in zebrafish [105]. ZHX1 and ZHX2 participate in the development and progression of several types of cancer, and the low expression of both impacts a poor prognosis in chronic lymphocytic leukemia [106].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to females, unique transcription factors regulators of switch genes from M-AD and M-asymAD were predominantly associated with cancers. For example, ZHX1, a unique transcription factor in M-AD, has been implicated in gastric cancer, chronic lymphocytic leukemia, and gliomas ( Ge and Li, 2020 ; You et al, 2020 ; Maciel et al, 2021 ). TCF7 is involved in prostate cancer ( Chen et al, 2015 ; Siu et al, 2017 ), and it is highly expressed in immune cells in atherosclerosis plaques ( Ma et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of ZHX1 and ZHX2 in chronic lymphocytic leukemia (CLL) has recently been reported [ 34 ]. CLL patients with reduced ZHX1 and ZHX2 expression have a worse prognosis.…”
Section: Oncogenic or Tumor-suppressive Functions Of Zhxs In Cancersmentioning
confidence: 99%